An Assessment of State‐of‐the‐Art Mean Sea Surface and Geoid Models of the Arctic Ocean: Implications for Sea Ice Freeboard Retrieval. Issue 11 (11th November 2017) - Skourup, Henriette; Farrell, Sinéad Louise; Hendricks, Stefan; Ricker, Robert; Armitage, Thomas W. K.; Ridout, Andy; Andersen, Ole Baltazar; Haas, Christian; Baker, Steven
Abstract: State‐of‐the‐art Arctic Ocean mean sea surface (MSS) models and global geoid models (GGMs) are used to support sea ice freeboard estimation from satellite altimeters, as well as in oceanographic studies such as mapping sea level anomalies and mean dynamic ocean topography. However, errors in a given model in the high‐frequency domain, primarily due to unresolved gravity features, can result in errors in the estimated along‐track freeboard. These errors are exacerbated in areas with a sparse lead distribution in consolidated ice pack conditions. Additionally model errors can impact ocean geostrophic currents, derived from satellite altimeter data, while remaining biases in these models may impact longer‐term, multisensor oceanographic time series of sea level change in the Arctic. This study focuses on an assessment of five state‐of‐the‐art Arctic MSS models (UCL13/04 and DTU15/13/10) and a commonly used GGM (EGM2008). We describe errors due to unresolved gravity features, intersatellite biases, and remaining satellite orbit errors, and their impact on the derivation of sea ice freeboard. The latest MSS models, incorporating CryoSat‐2 sea surface height measurements, show improved definition of gravity features, such as the Gakkel Ridge. The standard deviation between models ranges 0.03–0.25 m. The impact of remaining MSS/GGM errors on freeboard retrieval can reach several decimeters in parts of the Arctic. While the maximum observed freeboard difference found in the central Arctic was 0.59 m (UCL13 MSS minus EGM2008 GGM), the standard deviation in freeboard differences is 0.03–0.06 m. Key Points: A major advancement in mapping the Arctic Ocean mean sea surface (MSS) is realized through the inclusion of CryoSat‐2 data Sea ice freeboard retrievals from airborne/satellite altimeter measurements are impacted by the choice of MSS/GGM model used in the retrieval algorithm Depending on which MSS/GGM is used, the standard deviation of freeboard differences ranges 0.03–0.06 m, corresponding to an ice thickness uncertainty of 0.24–0.54 m